1998
DOI: 10.1002/(sici)1097-0142(19980301)82:5<936::aid-cncr20>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

GlutathioneS-transferase M1 and T1 and cytochrome P4501A1 polymorphisms in relation to the risk for benign and malignant head and neck lesions

Abstract: The occurrence of polymorphic variants in the GSTM1, GSTT1, and CYP1A1 genes did not differ between the groups investigated, therefore indicating no significant contribution to the development of head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Among them, 42 studies described the association between GSTM1 null genotype and HNSCC, and 32 between GSTT1 null genotype and HNSCC. For the association between dual null genotype and HNSCC, 1 discarded article [13] containing the distribution information of dual null genotype was reincorporated, and 15 studies were included (Table 1). For the analyses stratified by smoking, eight studies [5], [8], [29], [33], [45], [47], [48], [55] for GSTM1 , and seven studies [5], [33], [38], [45][48] for GSTT1 were included.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 42 studies described the association between GSTM1 null genotype and HNSCC, and 32 between GSTT1 null genotype and HNSCC. For the association between dual null genotype and HNSCC, 1 discarded article [13] containing the distribution information of dual null genotype was reincorporated, and 15 studies were included (Table 1). For the analyses stratified by smoking, eight studies [5], [8], [29], [33], [45], [47], [48], [55] for GSTM1 , and seven studies [5], [33], [38], [45][48] for GSTT1 were included.…”
Section: Resultsmentioning
confidence: 99%
“…They found an increased risk associated with the CYP1A1 3798CC genotype (OR = 2.39; 95% CI = 1.11–5.16), compared with the TT genotype [71]. In other investigations, no such association was found [7274]. In the Gronau et al report [75], a German case-control study, the authors found that the homozygous mutation and the MspI restriction site in exon 7 are present only once in the control group and that no patient revealed this genotype.…”
Section: Cytochrome P450 (Cyp450)mentioning
confidence: 99%
“…In analogy to lung cancer, the theory has been put forward that some CYP1A1 / GSTM1 genotype combinations predispose to higher risks of oesophageal and oral cavity cancer in smokers [89,91]. Others found an influence of CYP1A1, GSTM1 and GSTT1 polymorphisms on the development of head and neck cancer inconsistent [92][93][94].…”
Section: Head and Neck Cancermentioning
confidence: 99%